Analisis Prinsip Kesantunan Dalam Teks Anekdot Pada Buku Cerdas Cergas Berbahasa Dan Bersastra Indonesia Kelas X - Diyah Dhariyanti; Yunia Fajar Khumairoh Azmi; Araminta Putri Dewari; Sherly Anida Fahrina Putri; Tri Karyanti; Asep Purwo Yudi Utomo; Didi Pramono (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Oral and written communication is broad and free. However, the content in it must comply with applicable rules, one of which is the principle of politeness contained in three anecdotal texts entitled “Liburan Kuli Bangunan”, “Perundungan Tanda Sayang”, and “Korupsi Kecil”. Criticism in it is conveyed by paying attention to the principles of politeness. However, not all speech contained in the text meets the principles of politeness. Therefore, the author was moved to carry out an analysis of the principles of politeness in the anecdotal texts entitled “Liburan Kuli Bangunan”, “Perundungan Tanda Sayang”, and “Korupsi Kecil” contained in the Cerdas Cergas Berbahasa dan Bersastra Indonesia SMA/SMK Kelas X. This analysis aims to discover and examine further the principles of language politeness by the discipline of pragmatics. The approach used in this research is a qualitative descriptive approach. The results of data analysis were collected using reading and note-taking techniques. The results of the analysis in this research found 19 violations of politeness principles, dominated by violations of the thimble agreement. Apart from that, there is compliance with the principles of politeness, totaling 4 utterances, namely 2 on the thimble of agreement, and the other 2 on the thimble of humility and the thimble of feelings. With this research, it is hoped that it will be useful for providing understanding and as additional reference material for further research regarding the principles of language politeness in communication.